Production of modifier from recycled materials with stable fraction of diamond inclusions (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The method of obtaining a modifying admixture, which includes diamond inclusions from secondary raw materials by the method of multiple detonation, was considered, which ensured its stable condition for 4 years and made it possible to use the surfacing method to increase the mechanical and operational indicators of restorative indicators.
Keywords: modification; recovery; secondary raw materials; detonation; ammunition; charge